Comparison of two chemical models to induce hepatic preneoplasia in male Wistar rats - Vera, Marina Cecilia (2015)
BACKGROUND: One established model to induce hepatic preneoplasia (HP) (DEN 150) uses diethylnitrosamine (DEN) as initiator agent and 2-acetylaminofluorene (2-AAF) as a promoter drug. In addition, both chemicals cause liver cholestasis and fibrosis. AIM: We compared DEN 150 model with another adapted by us, DEN 200 to simplify the first one and to evaluate the effectiveness of both treatments to induce HP in rats. MATERIAL AND METHODS: Male Wistar rats were divided in 3 groups: controls; DEN 150 (rats received 2 doses of DEN, 150 mg/kg body weight, 2 weeks apart, and then 2-AAF, 20 mg/kg body weight, 4 doses per week during 3 weeks); and DEN 200 (rats received a single dose of DEN 200 mg/kg body weight, and 2 weeks apart 2-AAF, 20 mg/kg body weight, 2 doses per week during 3 weeks). Four hepatic enzymes, prothrombin time percentage, the number of bile ductules, total collagen amount, the number of altered hepatic foci (AHF) per liver and the percentage of liver occupied by foci were analyzed. Results. There were no differences in the number of AHF per liver between treated groups. Rats from DEN 200 group showed a significant diminution in the volume of liver occupied by foci. DEN 200 group had no fibrosis and better hemostatic conditions than DEN 150 group. Both groups developed cholestasis. CONCLUSION: In conclusion, both protocols are good alternatives to induce HP in rats and the new protocol proposed is an effective and a simple methodology to provide subclinic states of liver cancer.